Understanding Walking Behavior: Its Benefits and Barriers - Fadli, Fatmawati (Universitas Ahmad Dahlan, 2016)
AbstractÂ Health survey demonstrates that 5.3 million people each year experienced a premature death due to physical inactivity (Lee et al., 2012). Data from Department of Health (2004) revealed that in the United Kingdom more than 60% of adult males and 75% of adult females did not perform enough physical activity. Hence, to minimize this problem, currently, health practitioners are trying to encourage people to be more physically active, especially by promoting several types of exercise, including walking (Marshall et al., 2009; Hallal et al., 2012). Regular walking is one of the essential predictors for long-term physical and mental health benefit. Some recent studies mention that there are lots of advantages if adults can maintain their regular walking (Gunnell, Knuiman, Divitini, & Cormie, 2014; Morgan, Tobar, & Synder, 2010; Roe & Aspinall, 2011; Shiue, 2015; Nagai et al., 2011). Regular walking minimum 10,000 steps each day can burn as much as 400 calories so that it may help overweight or obesity people to reduce their weight (NHS, 2014). However, most of the people perceive walking as one form of transport rather than exercise; therefore, this reason discourages them to walk sufficiently for healthy life purpose (Darker et al., 2007).Keywords:Â walking, walking benefits, walking barriersÂ